The Predisposing Factors Of Personal Hygiene Behavior Of Women Of Childbearing Age In Preventing Leucorrhoea - -, Della Aprisa; -, Prehatin Trirahayu Ningrum; Rokhmah, Dewi (Jurnal Kesehatan Ibu dan Anak, 2023)
Abnormal vaginal discharge in women of childbearing age becomes worse if it is not treated immediately because it can cause ectopic pregnancy and infertility. The low level of knowledge on hygiene of the reproductive organs often results in women ignoring it and assuming that vaginal discharge is a common health problem. The aim of the study was to analyze the personal hygiene behavior of women of childbearing age in preventing leucorrhoea in the Muncar coastal area, Banyuwangi Regency. This type of research is a qualitative method using a case study approach (Case Studies). Informants in this study amounted to 30 people. The results showed that most of the main informants had knowledge about the meaning of leucorrhoea, its causes, signs and symptoms, and prevention of leucorrhoea. The main informants get knowledge through social media, health workers, and the people closest to them. A small number of key informants did not know about the meaning of leucorrhoea, its causes, signs and symptoms, and prevention of leucorrhoea due to a lack of health information from health workers, social media and close people. Suggestions for women of childbearing age should improve personal hygiene for themselves. Be more open and communicate well about vaginal discharge with health workers, family and close friends.